Biochar-amended soils: A water-saving strategy for quinoa cultivation in the Andes - Condori Ataupillco, Tatiana; Flores Marquez, Ricardo; Quispe Rodriguez, Juan; Quispe Matos, Kenyi Rolando; Velásquez Mantari, José; Solórzano Acosta, Richard Andi (John Wiley & Sons Inc., 2025)
Previous studies showed that biochar amended soils significantly enhanced the growth and yield of quinoa under water limitations. So it becomes an emerging agronomic strategy to consider for sustainable quinoa production. Biochar can specifically be considered for the area particularly receiving low annual rainfall and more vulnerable to current climate change conditions